REPRESENTASI DINAMIKA PEREDARAN MINUMAN KERAS DAN GANGGUAN KEAMANAN PUBLIK PAPUA SELATAN MELALUI INSTAGRAM SEBAGAI REAL-TIME PUBLIC ALERT SYSTEM: (Studi Akun Instagram @papua_selatan_update) - Dyana Hesti Kamila; Tajuddin, Mulyadi Alrianto; Suradinata, Poetri Enindah (Jurnal Restorative Justice, 2025)
The establishment of South Papua Province under Law Number 14 of 2022 represents a strategic effort to strengthen governance and public security in the region. This study aims to identify patterns of public security disturbances and their relationship with the circulation of alcoholic beverages, as well as to analyze the role of the Instagram account @papua_selatan_update as a real-time public alert system. Employing a socio-legal approach, the research integrates normative analysis of alcohol-control and public-order regulations with empirical content analysis of posts uploaded between January and November 2025. The findings indicate that most incidents of violence, traffic accidents, and disturbances are strongly linked to alcohol consumption, with recurring spatial-temporal patterns in high-risk areas during nighttime. Instagram functions as a rapid, accurate, and participatory information platform, although it is not yet connected to formal governmental systems. The study concludes that regulatory strengthening, intensified patrols in hotspot areas, and the development of an integrated digital reporting system are urgently needed.